Translation and psychometric properties of the Mandarin Chinese version of the COVID-19 Impact Scale in college students - Zhang, Qing; Liu, Yahui; Yang, Jinxin; Liu, Chengwei; Yin, Haoyu (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic has caused significant long psychological impacts that require a novel measurement tool to capture the changes in such impacts. To this end, the COVID-19 Impact Scale (CIS) was developed as an instrument to evaluate psychological responses associated with the pandemic, and has shown evidence of a one-factor structure. The CIS was initially created using an Korea University students sample, and has since been translated and validated in Turkish. A total of 504 College students, aged 17-25, took part in the study from two universities in Jinan, located in Shandong Province, Eastern China, via an online survey platform. They were administered the Chinese versions of the following self-report instruments: Mandarin Chinese CIS, Fear of COVID-19 Scale, Depression Anxiety Stress Scale-21 and Satisfaction With Life Scale. Moreover, a sample of 86 participants who provided their contact information and agreed to participate in the second-round survey were asked to reassess using the Mandarin Chinese CIS after a period of three weeks following the initial testing. Results showed that Mandarin Chinese CIS had good internal consistency and test-retest reliability. Additionally, the Mandarin Chinese CIS presented good criterion validity and estimates of convergent validity and incremental validity. In confirmatory factor analysis, the one-factor model showed an acceptable fit after incorporating correlations between error terms. Our findings suggest that the Mandarin Chinese CIS is a reliable and valid self-report tool that demonstrates robust psychometric properties and acceptable construct validity when used with a Chinese university students.